The use of structures of modification in written compositions as a possible measure of language growth among students of Eulogio Rodriguez Jr. High School in Quezon City - Munson, Purita (Zamora) 1921- (1967)
This study measures the language growth through the use of structures of modification in written compositions among the students in eleven public high schools of Quezon City. The results of the study show that there is no direct relationship between the increase in curriculum year and the number of structures of modification used.
Thesis (Master of Arts in Teaching (English))--University of the Philippines, Diliman.
Keywords: English language -- Study and teaching -- Philippines; English language -- Syntax